"Skoolordes" in stede van "bedelordes": "n Heroorweging van die toepaslikheid van die begrip mendīcāns in die (Afrikaanse) Middeleeuse vakregister - Beukes, Johann (HTS teologiese studies, 2021)
‘Skoolordes’ instead of ‘bedelordes’: A reconsideration of the applicability of the term mendīcāns in the (Afrikaans) Medieval register. In this article the applicability of the Latin present participle mendīcāns in the (Afrikaans) Medieval register, with reference to the development of the four mendicant orders in the Medieval Latin West from the early 13th century onward, is reconsidered. The term mendīcāns is customarily translated as mendicant in English and as bedelend in Afrikaans (including the terminological transition to bedelordes and bedelmonnike) and familial languages such as Dutch (bedelorden and bedelmonniken) and German (Bettelorden and Bettelmönche). While the English application is by its Latinised nature subtle and not explicitly value-laden (referring not to begging but to the Latin participle mendīcāns), this is not the case in the latter languages. In the translation and terminological application of mendīcāns as bedelend in these languages, the profoundly condescending and Medievalist-patronising notion of ‘begging’ (which is wholly different from ‘receiving alms’) becomes prevalent. When, however, the idea-historical development of the term mendīcāns is reconsidered (particularly in the context of the Franciscan interpretation of the relation between usus [sustainable use within the milieu of idealised corporate poverty; ordo habeat usum, per Bonaventure]) and dominium [private ownership]), and taking into account that bedel refers not to social reciprocity (as it should in this context) but to a form of static and unilateral economic action, it seems sensible to review the term, at least in the latter languages, by a less value-determined alternative, such as skool (school). The four mendicant orders originating in the first decades of the 13th century (the Augustinians, Carmelites, Dominicans and Franciscans), shared a prominent feature, apart from not allowing themselves to own private property and the fact that they were indeed dependent on local communities for material (explicitly non-financial) support, namely the administration and conservation of a unique educational system of studia or local ‘boarding schools’, which functioned in a Venn-diagrammatical relationship with the young universities of the 12th century onward. The studia contributed in an unparalleled way to the academic formation of undergraduate students throughout the Medieval West. Rather than fixating on a static and arbitrary economic notion such as bedel, the vibrant academic achievements of the mendicant orders should instead be considered as their epitomising common feature – and should accordingly be reflected as such in the term describing them.Contribution: This re-evaluation of the applicability of the Latin term mendīcāns in the Medieval register contributes to the development and ongoing refinement of the Medieval register in specifically the Afrikaans language, whereby the English translations ‘mendicant friar’ and ‘mendicant orders’, translated and applied from mendīcāns as bedelmonnike and bedelordes in Afrikaans, be henceforth instead referred to as skoolmonnike and skoolordes.